Particle-associated polycyclic aromatic hydrocarbons in the atmosphere of Hong Kong - M* Zheng; M* Fang (Water, Air, Soil Pollut., 2000)
Polycyclic aromatic hydrocarbons (PAHs) in total suspended particulates (TSP) collected at six rural and urban stations in Hong Kong from 1993–1995 using high volume air samplers were identified using GC-MS (gas chromatography-mass spectrometry). The results showed that the PAHs exhibited distinct spatial and seasonal variability. The total PAH content (PAH) in the samples ranged from 0.41 to 48 ng m-3. The unsubstituted analogs are the characteristic products of high temperature combustion processes. The highest average PAH was measured at the street-level station in Mong Kok indicating that vehicles were high PAHs contributors. The rural station at Hok Tsui exhibited the lowest PAH level, however; influences of city plumes could be seen when northerly or northeasterly winds prevailed in the winter. All stations experienced the highest loading of PAHs in autumn and the lowest in summer; the former was 2.8 times greater than the latter. This seasonal variability is due to the Asian monsoon system, precipitation, micrometeorology, and the rate of photodegradation. In summer, Hong Kong experiences relatively clean oceanic air and high rates of precipitation and photodegradation, while upon the onset of the winter monsoon, local air mass is replaced by polluted air streams from the Asian continent. Benzo(b)fluoranthene, benzo(k)fluoranthene, benzo(e)pyrene, indeno(1,2,3-cd)pyrene and benzo(ghi)perylene were the dominant species in the samples. The PAH distribution patterns at different stations were similar within each season. However, seasonal variations existed. For example, phenanthrene contributed up to 14% of the total PAH in summer, while the dominance of benzo(b)fluoranthene, benzo(k)fluoranthene was more significant in autumn and winter.